2011
DOI: 10.1111/j.1541-4337.2011.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Blueberries and Their Anthocyanins: Factors Affecting Biosynthesis and Properties

Abstract: Blueberry is one of the most popular fruits in North America and rich in anthocyanins. Its content in anthocyanins contributes to the health-beneficial effects of blueberry against several chronic diseases including cardiovascular disorders, neurodegenerative diseases, diabetes, and cancer. This paper summarizes various facts presenting blueberry as a fruit with huge potential for increased future consumption as a health-enhancing food. Factors affecting the biosynthesis of the various anthocyanins in blueberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(136 citation statements)
references
References 180 publications
(289 reference statements)
1
130
0
5
Order By: Relevance
“…Duke was confi rmed as a valuable source of potentially healthy compounds; in fact, the total anthocyanin content at harvest was of 223.86 mg C 3 G /100 g FW. Although many studies have been performed, the effects of the storage time and temperature on the behavior of the anthocyanin contents are not well known [Kalt et al, 1999;Routray & Orsat, 2011] and the CO 2 -enriched atmospheric effects on their stability are also uncertain [Wang, 2007]. Our data show that for all fi lms used, the degradation rate of anthocyanins increases as the temperature rises according to previous studies [Routray The data were expressed on means(%)±standard error.…”
Section: Total Anthocyanin and Phenolic Contents And Antioxidant Actisupporting
confidence: 63%
“…Duke was confi rmed as a valuable source of potentially healthy compounds; in fact, the total anthocyanin content at harvest was of 223.86 mg C 3 G /100 g FW. Although many studies have been performed, the effects of the storage time and temperature on the behavior of the anthocyanin contents are not well known [Kalt et al, 1999;Routray & Orsat, 2011] and the CO 2 -enriched atmospheric effects on their stability are also uncertain [Wang, 2007]. Our data show that for all fi lms used, the degradation rate of anthocyanins increases as the temperature rises according to previous studies [Routray The data were expressed on means(%)±standard error.…”
Section: Total Anthocyanin and Phenolic Contents And Antioxidant Actisupporting
confidence: 63%
“…Substitution of 30 % of gluten-free flour mixture with different proportion of raspberry and blueberry pomace led to increase in cookies darkness and redness and decrease in yellowness (data not shown). The increase of blueberry pomace content in cookie formulation led to decrease in b * values, indicating the presence of characteristic blue anthocyanins such as 3-glycosidic derivatives of delphinidin, malvidin and petunidin (Routray and Orsat 2011). Addition of raspberry pomace in formulation increased the redness of cookies, due to the presence of characteristic red pigment cyaniding-3-sophoroside (Chen et al 2007).…”
Section: Color Of the Cookiesmentioning
confidence: 99%
“…Previous studies demonstrated that plants with high content of anthocyanins, had significant antibacterial effect (Hearst et al, 2010). In vitro studies indicate that anthocyanins and other polyphenols in berries could be substantial in the treatment of heart disease (Basu et al, 2010;Routray and Orsat, 2011), including antioxidant (Denev et al, 2010) and antiadhesion activity against bacteria (Huttunen et al, 2011). Compounds such as quercetin and phenolic acids could play an important role in the possible health effects of berries (Paredes-López et al, 2010).…”
Section: Introductionmentioning
confidence: 99%